4(x+7)+3(3x-7)=72

Simple and best practice solution for 4(x+7)+3(3x-7)=72 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+7)+3(3x-7)=72 equation:


Simplifying
4(x + 7) + 3(3x + -7) = 72

Reorder the terms:
4(7 + x) + 3(3x + -7) = 72
(7 * 4 + x * 4) + 3(3x + -7) = 72
(28 + 4x) + 3(3x + -7) = 72

Reorder the terms:
28 + 4x + 3(-7 + 3x) = 72
28 + 4x + (-7 * 3 + 3x * 3) = 72
28 + 4x + (-21 + 9x) = 72

Reorder the terms:
28 + -21 + 4x + 9x = 72

Combine like terms: 28 + -21 = 7
7 + 4x + 9x = 72

Combine like terms: 4x + 9x = 13x
7 + 13x = 72

Solving
7 + 13x = 72

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 13x = 72 + -7

Combine like terms: 7 + -7 = 0
0 + 13x = 72 + -7
13x = 72 + -7

Combine like terms: 72 + -7 = 65
13x = 65

Divide each side by '13'.
x = 5

Simplifying
x = 5

See similar equations:

| (3x+4)(4x+1)-(2x+3)(x+3)=(5x+2)(2x+1) | | 14x-18=12-6x | | -4x-150=66-12x | | 0.19y+0.06(y+6000)=1860 | | 8x+16y=640 | | 3/4*b=8 | | 5s=4 | | -7y+3= | | 6x-y=-23 | | -2u=-2/9 | | -6(-3y+6)-4y=5(y-8)-2 | | 7-2b=2b+6 | | Y=17-4y-2 | | x/4=5/12-6-x/15 | | -3v+6v=-20-1 | | 1/4(20d-16)=5d-4 | | -9+11=6x-8x | | X=21/5/8 | | 1/3(6-3a)=6 | | (2/(16x^2-4))-(2/(8x^2-8x-6)) | | 45-15=5(x-6) | | (3n+1)(n+3)+5=40 | | 7^-3/x^-2 | | 7q-13=3q+3 | | -4+3(-6n-1)=-2(-4n+5)-2 | | 5x+7.5= | | 30x-12=12x-6 | | 4y=-3.8 | | .35+3x=.45+2x | | -2y+6+3y=6 | | 5x+7(-x-10)=-82 | | 5-a=18 |

Equations solver categories